True vaginal prolapse associated with retroflection of the urinary bladder in a bitch - Beretta, Samara [UNESP]; Apparicio, Maricy [UNESP]; Moraes, Paola de Castro [UNESP]; Ribeiro, Camila Vasconcelos; Estevam, Marina Vilela [UNESP]; Smargiassi, Nathalia Franzoni; Maronezi, Marjury Cristina; Bonacin, Yuri da Silva; Toniollo, Gilson Helio [UNESP]; Gimenes, Lindsay Unno [UNESP] (Canadian Vet Med Assoc, 2023)
True vaginal prolapse is rare in bitches and is most likely to occur near whelping. A 2-year-old intact female Brazilian mastiff, 39.5 kg, had a true vaginal prolapse associated with urinary bladder retroflection; the female was in estrus, and concomitantly had diarrhea for 3 d, plus vaginal hyperplasia, and ultimately a vaginal prolapse. Ultrasound examination and retrograde urethrocystography were extremely important for detection and identification of the position (retroflection) of the urinary bladder within the prolapsed vagina. These tools, therefore, are recommended for a conclusive diagnosis and surgical planning, to avoid trans- and postoperative complications, e.g., urethral damage or bladder rupture. Prompt diagnosis and surgical correction enabled a favorable prognosis and rapid postoperative recovery, avoiding complications or ultimately death of the dog.